2008
DOI: 10.1590/s0103-50532008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymer- hydrogel blends for electrochemically controlled drug release devices

Abstract: Blendas formadas pela polimerização eletroquímica de pirrol em matriz de acrilamida (hidrogel) foram utilizadas, neste trabalho, como dispositivos para a liberação controlada de drogas. A influência de vários parâmetros nesta síntese, como tipo de matriz de hidrogel e condições de polimerização, foi estudada empregando-se planejamento fatorial fracionário. O objetivo final consistiu na obtenção de um material adequado para liberação baseada no controle de potencial. Para os testes de liberação foi utilizada Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…A number of drug release profiles have been obtained, which demonstrate that CP-hydrogel materials can be used to deliver biomolecules and drugs to tissues [25,108,111]. Small et al [111] released calcon (solochrome dark blue, MW = 416.38 Da) from a Polyacrylamide-PPy gel, and Barthus et al demonstrated release of safranin (MW = 350.84 Da) from PPy-polyacrylamide [108].…”
Section: Control Of Biomolecule Releasementioning
confidence: 99%
See 1 more Smart Citation
“…A number of drug release profiles have been obtained, which demonstrate that CP-hydrogel materials can be used to deliver biomolecules and drugs to tissues [25,108,111]. Small et al [111] released calcon (solochrome dark blue, MW = 416.38 Da) from a Polyacrylamide-PPy gel, and Barthus et al demonstrated release of safranin (MW = 350.84 Da) from PPy-polyacrylamide [108].…”
Section: Control Of Biomolecule Releasementioning
confidence: 99%
“…Small et al [111] released calcon (solochrome dark blue, MW = 416.38 Da) from a Polyacrylamide-PPy gel, and Barthus et al demonstrated release of safranin (MW = 350.84 Da) from PPy-polyacrylamide [108]. Both of these studies showed acute release profiles across 250 and 400 min, respectively and it is likely that longer-term profiles would be required for most chronic implants.…”
Section: Control Of Biomolecule Releasementioning
confidence: 99%
“…This experiment is of relevant importance because is a clear indication of the electroactivity of the composite and the possibility of tuning the swelling behavior by the application of an electric field. In order to investigate the release kinetics and the possibility of electrochemical control, safranine was chosen as model molecule due to its size, structure and with the sake of comparison with former works performed in our group involving other composites such as polyacrylamide/PPy and Polycrylamide/PANI [22][23][24] Release profiles can be analyzed by using a molecular model on the light of the Fick's law. Hitger and Peppas [28] proposed a model that describes the solute delivery mechanism from polymeric materials that is represented by the Equation (2):…”
Section: Resultsmentioning
confidence: 99%
“…As an example, our group has demonstrated the synthesis of a polyaniline-polyacrylamide composite by electropolymerization of conducting polymer inside an insulating hydrogel matrix of different pore sizes. This resulting new material was successfully applied in electrochemical controlled release devices [22][23][24]. A number of examples of synthesis and application of ECHs can be found in a recent review on this topic [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Their potential has been demonstrated in a broad range of applications, such as in energy conversion and storage devices, supercapacitors, sensors, bioelectronics and medical electrodes. [20][21][22][23] The incorporation of CPs, such as polypyrrole, polyaniline and polythiophene, with a variety of polymers, metals, membranes and bioactive molecules, has been extensively studied due to their ease of synthesis, processability, and excellent environmental stability. [24][25][26] However, CPs are difficult to further modify after synthesis using post-processing methods, because they are normally non-thermoplastic, mechanically rigid and insoluble.…”
Section: Introductionmentioning
confidence: 99%